Development Strategy of Knowledge's Nationalism and Tolerance for Indonesia's Young Generation: A Case Study of Flag-Raising Troop (Paskibraka) - Prabowo, M. Akbar Hadi; Wasino, Wasino; Pramono, Suwito Eko; Kurniawan, Edi (Universitas Negeri Semarang, 2024)
This research aims to analyze how the participation of Paskibraka members influences their attitudes towards unity and tolerance amidst Indonesia's cultural diversity. Paskibraka, as a youth organization playing a crucial role in state ceremonies, not only prepares its members for ceremonial duties but also fosters the internalization of values of nationalism and tolerance. This study employs a qualitative method with a case study approach, involving in-depth interviews with Paskibraka members and field observations during their educational and training camps. The research findings indicate that participation in Paskibraka provides profound experiences for its members, where they learn to appreciate national symbols and understand the importance of unity and diversity. Paskibraka members also engage in social activities that promote national values and tolerance, significantly strengthening their national identity. The study found that the direct experience of raising the national flag and involvement in social activities enhances members' awareness of the importance of unity and tolerance, as well as developing an inclusive attitude towards cultural differences. These findings highlight the importance of supporting extracurricular programs like Paskibraka in the national education system to shape young generations with a spirit of patriotism and a commitment to diversity.